A diffuse idiopathic skeletal hyperostosis case misdiagnosed as ankylosing spondylitis - Alkan, Gökhan; Gülkesen, Arif; Akgöl, Gürkan; Gur, Canan; Kaya, Arzu (My University, 2017)
Diffuse idiopathic skeletal hyperostosis (DISH) is a rheumatologic disease with unknown etiology characterized with ossifications of columna vertebralis. Signs and symptoms include stiffness, pain and movement limitation of spine. The radiographic diagnostic criteria in the spine include osseous bridging along the anterolateral aspect of at least four vertebral bodies, relative sparing of intervertebral disc heights with minimal or absent disc degeneration, and absence of apophyseal joint ankylosis and sacroiliac sclerosis. The diagnosis of DISH can be confused with ankylosing spondylitis (AS) because of some common clinical and radiological characteristics. In this paper a diffuse idiopathic skeletal hyperostosis case misdiagnosed as ankylosing spondylitis is reported.
Keywords: Genel ve Dahili Tıp; Romatoloji